Penerapan Panel Surya untuk Penerangan Kapal Kelompok Nelayan Pantai Jaya, Padang - Habibullah Habibullah; Rahmat Hidayat; Pinto Anugrah (Jurnal Teknik Elektro Indonesia, 2020)
Pasie Nan Tigo Urban Village has 20 Fishermen Groups, one of which is active is the Pantai Jaya Fishermen Group. Based on the facts and discussions with the Pantai Jaya Fishermen group it was found that the most important problem was the high operational costs required when going to sea, while the fish catches obtained were uncertain and the lack of technological touch in the fishing process. To go to sea, fishermen with Tondo Ships must prepare a minimum fund of 1.35 million rupiah, of which around 50% is used to buy fuel oil (BBM). The solution offered to solve the problem is the utilization of environmentally friendly solar energy through the solar panel technology of ship lighting systems. It is expected that from this activity can be obtained by fishing boats powered by environmentally friendly solar energy that is more economical and profitable. The use of solar panels for ship lighting systems will replace the use of generator engines which so far need fuel.